LEGAL PROTECTION FOR DOCTORS IN PROVIDING HEALTH SERVICES AT THE COMMUNITY HEALTH CENTER OF BENER MERIAH DISTRICT - Desy Radhiyah; Dahlan; Tamaulina Br. Sembiring (PT. Radja Intercontinental Publishing, 2024)
This study attempts to examine the Legal Protection for Doctors in Providing Health Services at the Bener Meriah Regency Health Center. A doctor in carrying out his profession will very likely get a situation that leads to the realm of law, it can be due to the final result of a treatment process carried out by the doctor which if the patient who is being treated dies or is disabled, it could get a response from the patient's family that this is malpractice. The problems written in this study are: How is the inpatient health service system at the Bener Meriah Regency Health Center, what are the factors of inpatient health services that can bring doctors at the Bener Meriah Regency Health Center into the realm of law, How is the legal protection for doctors in providing inpatient health services at the Bener Meriah Regency Health Center. This research is a qualitative research that is descriptive in nature with an empirical legal approach whose data consists of primary data and secondary data, then primary data is taken through interviews and secondary data sourced from legal materials based on concepts, theories, laws and regulations. The research shows that the inpatient health service system at the health center that was the object of the research has carried out and provided maximum and quality health services for the local community, and has carried out its duties in accordance with the applicable SOP, while the factors that can bring doctors into the legal realm are referral factors, availability of equipment and drugs, and visas requested by members of the community, legal protection is given to doctors who treat patients at the health center in Bener Meriah Regency after being assessed as having carried out their duties properly.